Implementasi Multikultural Siswa Dalam Pembelajaran Pendidikan Agama Islam di Sekolah Dasar Negeri Cipayung 04 - Heryati, Salsabillah Ayu; Akil, Akil; Ramdhani, Khalid (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze the implementation of Islamic religious education with a multicultural perspective in elementary schools. The research was conducted at Cipayung 04 Public Elementary School. The research method used a qualitative case study. Sources of data teachers, principals, and students. The research instrument used interviews, observation and documentation. Data analysis techniques include: data collection, data reduction, data verification and data display. The results of the multicultural-based implementation of Islamic religious education research through: 1) The new student admission policy does not discriminate between ethnicity, race and religion; 2) Implementation of learning upholds the values ​​of mutual respect, openness, compassion, conflict resolution and reconciliation and violence; 3) Realizing tolerance in religious life in life between all members of the community in daily life in the school environment. Multicultural values ​​are a process of acquiring knowledge, developing attitudes and behavior to live in mutual respect, tolerance, full of peace, mutual assistance and non-violence. Islamic religious education is education that focuses more on improving the mental attitude that is manifested in actions, both for the needs of oneself and others, both theoretically and practically. This research focuses on three studies, firstly all forms of multicultural values ​​in learning Islamic religious education at Cipayung 04 Public Elementary School. So it is related to efforts regarding multicultural-based learning so far because the school does not have multiculturalism, the school places more emphasis on character education. One of education, cultural education can be in the form of mutual cooperation, mutual respect, responsibility, discipline. So character education is very important to achieve quality education for students. If the character has been formed early on in order to make quality and qualified students. And in practice learning is also more respectful and tolerant among peers, in learning it emphasizes Pancasila values ​​in respecting diversity.